RELATIONSHIP BETWEEN VITAMIN D, CALCIUM, PARATHYROID HORMONE AND ALKALINE PHOSPHATASE AMONG PATIENTS INVESTIGATED FOR VITAMIN D - MOHAMMAD, JAMAL BASHER (Journal of Duhok University, 2021)
INTRODUCTION: Vitamin D deficiency causes rickets in young children and Osteomalacia in adults. Parathyroid hormone (PTH) secretion, Calcium level and Alkaline phosphatase (ALP), elevated in cases of low level of VD. This study to detect the relationship between serum VD, (PTH), calcium and ALP. Serum 25OHD is regarded as the best indicator of VD status. METHODS: The current study is a retrospective descriptive study in Azadi Teaching Hospital- Duhok Governorate – Kurdistan Region / Iraq. Out of 870 patients were included in the study. All VD requests were analysed, Calcium, ALP, PTH, and phosphate were recorded. RESULTS: Fifty-nine percent of the requests were for females, and 27.9% of the included patients were receiving VD supplementation. The mean values for serum 25OHD and PTH levels were 34.5 nmol / L (13.8ng/ml) and 53.4pg / ml respectively. Serum 25OHD was below 25 nmol / L in (227 / 870) 26.09 %, between 25 - 50 nmol / L in (391/ 870) 44.94%, and > 50 in (252 / 870) 28.96%. Out of 227 patients with VD deficiency (< 25nmol / L), only 1(0.44%) had hypocalcaemia, 28 (12.33%) had abnormal high ALP, 109 (48%) had abnormal high PTH. Out of 252 patients with VD level > 50 nmol / L, 63 (25%) were found to have high PTH, 21 (8.33%) with high ALP, hypocalcaemia were found in 1(0.39%) and low phosphate were found in 7(2.77 %) of the patients. Out of 391 patients with normal VD (< 25.1 -50 nmol / L), only 3 (0.76%) had hypocalcaemia, 30 (7.67%) had abnormal high ALP, and 154 (39.38%) had abnormal high PTH. CONCLUSION: A normal Calcium level, ALP and/or PTH will not exclude 25OHD deficiency and measurement of 25OHD should be performed whenever VD deficiency is expected